Outcomes at follow-up of negative colonoscopy in average risk population: systematic review and meta-analysis - Heisser, Thomas; Peng, Le; Weigl, Korbinian; Hoffmeister, Michael; Brenner, Hermann (The BMJ, 2019)
Objective To review and summarise the evidence on the prevalence of colorectal adenomas and cancers at a follow-up screening colonoscopy after negative index colonoscopy, stratified by interval between examinations and by sex. - Design Systematic review and meta-analysis of all available studies. - Data sources PubMed, Web of Science, and Embase. Two investigators independently extracted characteristics and results of identified studies and performed standardised quality ratings. - Eligibility criteria Studies assessing the outcome of a follow-up colonoscopy among participants at average risk for colorectal cancer with a negative previous colonoscopy (no adenomas). - Results 28 studies were identified, including 22 cohort studies, five cross sectional studies, and one case-control study. Findings for an interval between colonoscopies of one to five, five to 10, and more than 10 years were reported by 17, 16, and three studies, respectively. Summary estimates of prevalences of any neoplasm were 20.7% (95% confidence interval 15.8% to 25.5%), 23.0% (18.0% to 28.0%), and 21.9% (14.9% to 29.0%) for one to five, five to 10, and more than 10 years between colonoscopies. Corresponding summary estimates of prevalences of any advanced neoplasm were 2.8% (2.0% to 3.7%), 3.2% (2.2% to 4.1%), and 7.0% (5.3% to 8.7%). Seven studies also reported findings stratified by sex. Summary estimates stratified by interval and sex were consistently higher for men than for women. - Conclusions Although detection of any neoplasms was observed in more than 20% of participants within five years of a negative screening colonoscopy, detection of advanced neoplasms within 10 years was rare. Our findings suggest that 10 year intervals for colonoscopy screening after a negative colonoscopy, as currently recommended, may be adequate, but more studies are needed to strengthen the empirical basis for pertinent recommendations and to investigate even longer intervals. - Study registration Prospero CRD42019127842.